No neutral ground: South Africa's confrontation with the activist churches (Africa Watch Report, 1989)
The South African government has repeatedly subjected South African churches active in human rights work to severe repression. This report documents the cases of more than one hundred clergy and church workers who have been detained since 1980, some for more than two years; some have been severely tortured